2010
DOI: 10.1038/ajg.2010.201
|View full text |Cite|
|
Sign up to set email alerts
|

Pancrelipase Delayed-Release Capsules (CREON) for Exocrine Pancreatic Insufficiency due to Chronic Pancreatitis or Pancreatic Surgery: A Double-Blind Randomized Trial

Abstract: Pancrelipase delayed-release 12,000-lipase unit capsules were effective in treating fat and nitrogen maldigestion with a TEAE rate similar to that of placebo in patients with EPI due to CP or PS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
1
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 30 publications
3
116
1
17
Order By: Relevance
“…Improvement, but incomplete resolution of subjective and objective steatorrhea was reported. In addition, PERT also had a higher incidence of adverse drug reactions like pain, dyspepsia, and flatulence [81][82][83][84].…”
Section: Randomized Controlled Trials Of Pert In Patients With Pancrementioning
confidence: 99%
“…Improvement, but incomplete resolution of subjective and objective steatorrhea was reported. In addition, PERT also had a higher incidence of adverse drug reactions like pain, dyspepsia, and flatulence [81][82][83][84].…”
Section: Randomized Controlled Trials Of Pert In Patients With Pancrementioning
confidence: 99%
“…10 However, few reports have evaluated the potential of pancrelipase to improve hepatic steatosis. 8 In this study, we evaluated whether pancrelipase or other digestive enzymes could improve hepatic steatosis after pancreatic resection.…”
mentioning
confidence: 99%
“…Brägelmann et al [17] found an improvement in the overall well-being, whereas no differences in individual symptom scores were observed. It should be noted that both studies used very different dosages, with one study only substituting one third of the proposed necessary levels [16,24] . Whether this is sufficient enough to reach functional levels is unclear; the minimum doses of lipase that are considered are in the range of 25,000-50,000 units of lipase/meal [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent RCTs supported the supplementation of pancreatic enzymes in patients with exocrine pancreatic insufficiency due to chronic pancreatitis or pancreatic surgery [23,24] . Based on these findings, the findings of decreased pancreatic function after total gastrectomy supplementation with pancreatic enzymes to help relieving of the symptoms is on trial.…”
Section: Discussionmentioning
confidence: 99%